Effect of platelet activating factor antagonist treatment on gentamicin nephrotoxicity - A. Rodriguez-Barbero; E. Bosque; L. Rivas-Cabaero; M. Arévalo; J. M. López-Novoa (Mediators of Inflammation)
To assess whether PAF could be involved in the gentamicin-induced nephrotoxicity, we have studied the effect of PAF antagonist BN-52021 on renal function in rats after gentamicin (GENTA) treatment. Experiments were completed in 21 Wistar rats divided into three groups: group GENTA was injected with gentamicin 100 mg kg−1 body wt/day s.c. for 6 days. Group GENTA + BN received gentamicin and BN-52021 i.p. 5 mg kg−1 body wt/day. A third group served as control. Rats were placed in meta-bolic cages and plasma creatinine and creatinine clearance were measured daily. GENTA group showed a progressive increase in plasma creatinine, a drop in creatinine clearance and an increase in urinary excretion of N-acetyl-β-D-glucosaminidase and alkaline phosphatase. GENTA + BN group showed a lesser change in plasma creatinine and a creatinine clearance, but no difference with GENTA group in urinary excretion of NAG and AP were observed. Histological examination revealed a massive cortical tubular necrosis in rats treated with gentamicin, whereas in BN-52021 injected animals tubular damage was markedly attenuated. The present results suggest a role for PAF in the gentamicininduced nephro-toxicity.